Hot-stamped steel sheet and hot-stamped molded body

By controlling the chemical composition and metal structure of the steel sheet used for hot stamping, the problem of insufficient bending of hot stamped parts was solved, and hot stamped parts with high strength and excellent bending properties were realized, meeting the requirements of lightweight and collision characteristics of automotive components.

CN116917524BActive Publication Date: 2026-01-13NIPPON STEEL CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280018830.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-05-13
Filing Date
2022-05-09
Publication Date
2026-01-13
Estimated Expiration
2042-05-09

AI Technical Summary

Technical Problem

While existing hot stamping forms improve tensile strength, they lack flexibility, making it difficult to achieve a higher level of vehicle body lightweighting.

Method used

By controlling the chemical composition and microstructure of hot-stamped steel sheets, the combined area ratio of ferrite and granular bainite in the steel sheets is ensured to be above 10% and below 50%, with a ratio between 0.30 and 0.70. The average grain size of the old austenite grains is controlled to be 5–25 μm, with a standard deviation of 0.1–2.0 μm, thereby improving the flexibility of the steel sheets.

Benefits of technology

It achieves high strength and excellent flexibility, meets the requirements of lightweight and impact characteristics for automotive components, and improves the overall performance of hot-stamped parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005657822510000241
    Figure GDA0005657822510000241
  • Figure GDA0005657822510000251
    Figure GDA0005657822510000251
  • Figure GDA0005657822510000261
    Figure GDA0005657822510000261
Patent Text Reader

Abstract

The hot-stamping steel sheet of the present invention has a specified chemical composition and has an area ratio of ferrite S. α and the area ratio S of granular bainite GB The total is S α +S GB The area ratio S of granular bainite is 10% or more but less than 50%. GB The above-mentioned area ratio S of ferrite α The ratio is S GB / S α The metal structure is 0.30 to 0.70. Furthermore, the hot-stamped formed body manufactured from this hot-stamping steel sheet has a specified chemical composition, a metal structure with an average grain size of 5 to 25 μm of old austenite grains and a standard deviation of 0.1 to 2.0 μm of the grain size distribution of old austenite grains, and a tensile strength of 2200 MPa or more.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a hot-stamped steel sheet and a hot-stamped formed body.

[0002] This application claims priority based on Japanese Patent Application No. 2021-081620 filed on May 13, 2021, and the contents thereof are hereby incorporated by reference. BACKGROUND

[0003] In the past, from the viewpoint of the global environmental problem and the collision safety performance, thinning and high-strengthening of an automobile member have been required. In order to cope with these requirements, an automobile member using a high-strength steel sheet as a raw material has increased. In addition, as a forming method of a high-strength steel sheet, a method called hot stamping is known. In hot stamping, a high-strength steel sheet is subjected to press forming in a high temperature region of 700°C or higher, and is subjected to quenching inside or outside a press die. If hot stamping is used, since forming is performed in a high temperature region in which the strength of the steel sheet is low, forming defects such as those generated in cold press can be suppressed. In addition, since a microstructure in which a martensite is the main phase is obtained by quenching after forming, high strength can be obtained. Therefore, a hot-stamped formed body having a tensile strength of about 1500 MPa is widely used in the world.

[0004] In an automobile member formed by hot stamping a high-strength steel sheet, in order to obtain a higher effect of lightening a vehicle body, a member having high strength and excellent collision characteristics is required. In order to improve the collision characteristics of an automobile member, it is particularly required that the bendability of the automobile member be excellent.

[0005] In Patent Literature 1, a hot-stamped formed body having a tensile strength of 1900 MPa or higher and capable of suppressing low-stress fracture and a method for manufacturing the same are disclosed.

[0006] The present inventors have found that, in an automobile member in which the tensile strength is further improved, in order to obtain a higher effect of lightening a vehicle body, the bendability needs to be further improved.

[0007] PRIOR ART DOCUMENTS

[0008] PATENT LITERATURE

[0009] Patent Literature 1: International Publication No. 2018 / 134874

[0010] NON-PATENT LITERATURE

[0011] Non-Patent Literature 1: Acta Materialia, 58 (2010), 6393-6403 SUMMARY

[0012] PROBLEMS TO BE SOLVED BY THE INVENTION

[0013] The present application has been made in view of the above problem. An object of the present application is to provide a hot press-formed body having high strength and excellent bendability, and a hot press steel sheet capable of manufacturing the hot press-formed body.

[0014] Means for solving the problem

[0015] The gist of the present application is as described below.

[0016] [1] The chemical composition of the hot press steel sheet according to one aspect of the present application contains, in mass%:

[0017] C: more than 0.40% and 0.70% or less,

[0018] Si: 0.010 to 1.30%,

[0019] Mn: more than 0.60% and 3.00% or less,

[0020] P: 0.100% or less,

[0021] S: 0.0100% or less,

[0022] N: 0.0130% or less,

[0023] O: 0.0200% or less,

[0024] Al: 0.0010 to 0.500%,

[0025] Cr: 0.010 to 0.80%,

[0026] Nb: 0 to 0.100%,

[0027] Ti: 0 to 0.100%,

[0028] B: 0 to 0.0100%,

[0029] Mo: 0 to 1.00%,

[0030] Co: 0 to 2.00%,

[0031] Ni: 0% or more and less than 3.00%,

[0032] Cu: 0 to 1.00%,

[0033] V: 0 to 1.00%,

[0034] W: 0 to 1.000%,

[0035] Ca: 0 to 0.010%,

[0036] Mg: 0 to 1.000%,

[0037] REM: 0~1.000%

[0038] Sb: 0~1.000%

[0039] Zr: 0~1.000%

[0040] Sn: 0–1.000%, and

[0041] As: 0~0.100%,

[0042] The remaining portion contains Fe and impurities.

[0043] It has the following metal structure: ferrite area ratio S α and the area ratio S of granular bainite GB The total is S α +S GB It is between 10% and 50%.

[0044] The area ratio S of the above-mentioned granular bainite GB The above-mentioned area ratio S of ferrite α The ratio is S GB / S α The value ranges from 0.30 to 0.70.

[0045] [2] According to the hot stamping steel sheet described in [1] above, the above chemical composition may also contain, in mass %, selected from

[0046] Nb: 0.001~0.100%

[0047] Ti: 0.010~0.100%

[0048] B: 0.0015~0.0100%

[0049] Mo: 0.05–1.00%

[0050] Co: 0.05~2.00%

[0051] Ni: ≥0.01% and <3.00%

[0052] Cu: 0.01~1.00%

[0053] V: 0.01~1.00%

[0054] W: 0.001~1.000%

[0055] Ca: 0.001~0.010%

[0056] Mg: 0.001~1.000%

[0057] REM: 0.001 to 1.000%,

[0058] Sb: 0.005 to 1.000%,

[0059] Zr: 0.001 to 1.000%,

[0060] Sn: 0.001 to 1.000%, and

[0061] As: 0.001 to 0.100%

[0062] one or two or more kinds selected from the group consisting of

[0063] [3] The chemical composition of the hot press-molded body according to another aspect of the present application contains, in mass%:

[0064] C: more than 0.40% and 0.70% or less,

[0065] Si: 0.010 to 1.30%,

[0066] Mn: more than 0.60% and 3.00% or less,

[0067] P: 0.100% or less,

[0068] S: 0.0100% or less,

[0069] N: 0.0130% or less,

[0070] O: 0.0200% or less,

[0071] Al: 0.0010 to 0.500%,

[0072] Cr: 0.010 to 0.80%,

[0073] Nb: 0 to 0.100%,

[0074] Ti: 0 to 0.100%,

[0075] B: 0 to 0.0100%,

[0076] Mo: 0 to 1.00%,

[0077] Co: 0 to 2.00%,

[0078] Ni: 0% or more and less than 3.00%,

[0079] Cu: 0 to 1.00%,

[0080] V: 0 to 1.00%,

[0081] W: 0 to 1.000%,

[0082] Ca: 0 to 0.010%,

[0083] Mg: 0 to 1.000%,

[0084] REM: 0 to 1.000%,

[0085] Sb: 0 to 1.000%,

[0086] Zr: 0 to 1.000%,

[0087] Sn: 0 to 1.000%, and

[0088] As: 0 to 0.100%,

[0089] the remainder including Fe and impurities,

[0090] a metal structure having an average grain diameter of old austenite grains of 5 to 25 μm and a standard deviation of the grain diameter of the old austenite grains of 0.1 to 2.0 μm,

[0091] a tensile strength of 2200 MPa or more.

[0092] [4] The hot press-molded body according to the above [3], wherein the chemical composition can also contain, in mass%, at least one selected from the group consisting of

[0093] Nb: 0.001 to 0.100%,

[0094] Ti: 0.010 to 0.100%,

[0095] B: 0.0015 to 0.0100%,

[0096] Mo: 0.05 to 1.00%,

[0097] Co: 0.05 to 2.00%,

[0098] Ni: 0.01% or more and less than 3.00%,

[0099] Cu: 0.01 to 1.00%,

[0100] V: 0.01 to 1.00%,

[0101] W: 0.001 to 1.000%,

[0102] Ca: 0.001 to 0.010%,

[0103] Mg: 0.001 to 1.000%,

[0104] REM: 0.001 to 1.000%,

[0105] Sb: 0.005 to 1.000%,

[0106] Zr: 0.001 to 1.000%,

[0107] Sn: 0.001 to 1.000%, and

[0108] As: 0.001 to 0.100%

[0109] one or two or more kinds selected from the group consisting of

[0110] [5] The hot-stamped molded body according to the above-mentioned [3] or [4], wherein the area ratio of the above-mentioned old austenite grains having an average particle diameter of 0.5 to 3.0 μm can also be 60% or less.

[0111] Effects of the Invention

[0112] According to the above-mentioned aspect of the present invention, it is possible to provide a hot-stamped molded body having high strength and excellent bendability, and a hot-stamping steel sheet capable of manufacturing the same. DETAILED DESCRIPTION

[0113] The present inventors have studied the bendability of a hot-stamped molded body. As a result, the present inventors have found that, in the metal structure of a hot-stamped molded body, if fine old austenite grains exist in a large amount, the bendability deteriorates. In addition, the present inventors have found that, in the metal structure of a hot-stamped molded body, by setting the old austenite grains to a desired size, and suppressing the unevenness of the size of the old austenite grains, i.e., by making the old austenite grains uniform in size, it is possible to further improve the bendability of a hot-stamped molded body.

[0114] Next, the present inventors have studied a method for obtaining the above-mentioned hot-stamped molded body. As a result, the present inventors have found that, in the metal structure of a hot-stamping steel sheet, by generating a desired amount of ferrite and granular bainite, and controlling the area ratio of the ferrite and the area ratio of the granular bainite in a manner having a desired relationship, it is possible to obtain the above-mentioned hot-stamped molded body.

[0115] Hereinafter, the hot-stamping steel sheet and the hot-stamped molded body of the present embodiment based on the above-mentioned findings will be described. First, the reasons for limiting the chemical composition of the hot-stamping steel sheet of the present embodiment will be described.

[0116] Note that, regarding the numerical limitation range described with respect to the values described below with respect to the range of "to", the lower limit value and the upper limit value are included in the range. Regarding the values described as "less than" and "more than", the values are not included in the numerical range. Regarding the % of the chemical composition, all of them represent mass %.

[0117] The chemical composition of the hot-stamped steel sheet of the present embodiment contains, in mass%, C: more than 0.40% and 0.70% or less, Si: 0.010 to 1.30%, Mn: more than 0.60% and 3.00% or less, P: 0.100% or less, S: 0.0100% or less, N: 0.0130% or less, O: 0.0200% or less, Al: 0.0010 to 0.500%, Cr: 0.010 to 0.80%, and the remainder being Fe and impurities. Hereinafter, each element is described.

[0118] C: more than 0.40% and 0.70% or less

[0119] C greatly contributes to the improvement of the strength of the hot-stamped body. When the C content is 0.40% or less, it becomes difficult to obtain sufficient strength in the hot-stamped body. Therefore, the C content is set to more than 0.40%. It is preferable to be 0.42% or more, more preferable to be 0.45% or more, and further more preferable to be 0.47% or more.

[0120] On the other hand, when the C content is more than 0.70%, coarse carbides are generated and the bendability of the hot-stamped body deteriorates. Therefore, the C content is set to 0.70% or less. It is preferable to be 0.65% or less, and more preferable to be 0.60% or less.

[0121] Si: 0.010 to 1.30%

[0122] Si is an element that improves the deformability of the hot-stamped body by suppressing the generation of oxides that become the starting point of damage by combining with oxygen. When the Si content is less than 0.010%, coarse oxides are formed in the hot-stamped body and the desired bendability cannot be obtained. Therefore, the Si content is set to 0.010% or more. It is preferable to be 0.05% or more, and more preferable to be 0.10% or more.

[0123] On the other hand, when the Si content is more than 1.30%, coarse oxides are generated and the bendability of the hot-stamped body deteriorates. Therefore, the Si content is set to 1.30% or less. It is preferable to be less than 1.00%, and more preferable to be 0.50% or less.

[0124] Mn: more than 0.60% and 3.00% or less

[0125] Mn stabilizes austenite and improves the quenchability of the steel sheet. When the Mn content is 0.60% or less, sufficient quenchability cannot be obtained. Therefore, the Mn content is set to more than 0.60%. It is preferable to be 0.80% or more, and more preferable to be 1.20% or more.

[0126] On the other hand, when the content of Mn exceeds 3.00%, coarse inclusions are generated, and the bendability of the hot press-formed body deteriorates. Therefore, the content of Mn is set to 3.00% or less. It is preferable that the content of Mn be 2.20% or less, and more preferable that the content of Mn be 1.80% or less.

[0127] P: 0.100% or less

[0128] P segregates in the grain boundaries of the steel sheet, and the bendability of the hot press-formed body deteriorates. Therefore, it is preferable that the content of P be lower. In particular, when the content of P exceeds 0.100%, the workability of the steel sheet and the bendability of the hot press-formed body significantly deteriorate. Therefore, the content of P is set to 0.100% or less. It is preferable that the content of P be 0.080% or less, and more preferable that the content of P be 0.020% or less.

[0129] The lower limit of the content of P is not particularly limited, but can also be 0%. However, when the content of P is reduced to less than 0.0001%, the cost of dephosphorization significantly increases, and is not preferable in terms of economy. Therefore, the content of P can also be set to 0.0001% or more.

[0130] S: 0.0100% or less

[0131] S forms coarse inclusions, and the bendability of the hot press-formed body deteriorates. Therefore, it is preferable that the content of S be lower. In particular, when the content of S exceeds 0.0100%, the formability of the steel sheet and the bendability of the hot press-formed body significantly deteriorate. Therefore, the content of S is set to 0.0100% or less. It is preferable that the content of S be 0.0050% or less, and more preferable that the content of S be 0.0010% or less.

[0132] The lower limit of the content of S is not particularly limited, but can also be 0%. However, when the content of S is reduced to less than 0.0001%, the cost of desulfurization significantly increases, and is not preferable in terms of economy. Therefore, the content of S can also be set to 0.0001% or more.

[0133] N: 0.0130% or less

[0134] N forms coarse nitrides, and the bendability of the hot press-formed body deteriorates. Therefore, it is preferable that the content of N be lower. In particular, when the content of N exceeds 0.0130%, the formability of the steel sheet significantly deteriorates. Therefore, the content of N is set to 0.0130% or less. It is preferable that the content of N be 0.0100% or less or 0.0070% or less, and more preferable that the content of N be 0.0040% or less.

[0135] The lower limit of the content of N is not particularly limited, but can also be 0%. However, when the content of N is reduced to less than 0.0001%, the cost of denitrification significantly increases, and is not preferable in terms of economy. Therefore, the content of N can also be set to 0.0001% or more.

[0136] O: 0.0200% or less

[0137] O forms a coarse oxide in the steel, which deteriorates the bendability of the hot press-formed body. Therefore, the lower the O content, the more preferable. In particular, if the O content exceeds 0.0200%, the bendability of the hot press-formed body is significantly deteriorated. Therefore, the O content is set to 0.0200% or less. It is preferable to be 0.0100% or less, and more preferable to be 0.0060% or less.

[0138] The lower limit of the O content is not particularly limited, but can also be 0%. However, if the O content is reduced to less than 0.0001%, the manufacturing cost significantly increases, which is not preferable in terms of economy. Therefore, the O content can also be set to 0.0001% or more.

[0139] Al: 0.0010 to 0.500%

[0140] Al is an element that improves the deformability by suppressing the generation of oxides that are the starting points of damage, and improves the bendability of the hot press-formed body, by deoxidizing the molten steel. If the Al content is less than 0.0010%, deoxidization is not sufficiently performed, coarse oxides are generated, and the above effects cannot be obtained. Therefore, the Al content is set to 0.0010% or more. It is preferable to be 0.010% or more, and more preferable to be 0.030% or more.

[0141] On the other hand, if the Al content exceeds 0.500%, coarse oxides are generated in the steel, and the bendability of the hot press-formed body is reduced. Therefore, the Al content is set to 0.500% or less. It is preferable to be 0.450% or less, and more preferable to be 0.350% or less.

[0142] Cr: 0.010 to 0.80%

[0143] Cr improves the strength of the hot press-formed body by being solid-solved in the old austenite grains in heating at the time of hot pressing. If the Cr content is less than 0.010%, the effect cannot be obtained. Therefore, the Cr content is set to 0.010% or more. It is preferable to be 0.10% or more, and more preferable to be 0.20% or more.

[0144] On the other hand, if the Cr content exceeds 0.80%, coarse carbides are formed, and the bendability of the hot press-formed body is deteriorated. Therefore, the Cr content is set to 0.80% or less. It is preferable to be 0.60% or less, and more preferable to be 0.40% or less.

[0145] The remaining portion of the chemical composition of the hot press steel sheet of the present embodiment can also be Fe and impurities. As the impurities, elements that are mixed from the steel raw material or scrap and / or that are inevitably mixed in the steelmaking process, or elements that are allowed within a range that does not hinder the characteristics of the hot press-formed body of the present embodiment can be exemplified.

[0146] The hot-stamped steel sheet of the present embodiment can also contain the following elements as optional elements instead of part of Fe. The content in the case where the following optional elements are not contained is 0%.

[0147] Nb: 0 to 0.100%

[0148] Nb forms a carbonitride in the steel, and increases the strength of the hot-stamped body through precipitation strengthening. In order to obtain this effect, the Nb content is preferably set to 0.001% or more.

[0149] On the other hand, if the Nb content exceeds 0.100%, a large amount of carbonitride is generated in the steel, and the bendability of the hot-stamped body is reduced. Therefore, the Nb content is set to 0.100% or less.

[0150] Ti: 0 to 0.100%

[0151] Ti, like Nb, forms a carbonitride in the steel, and increases the strength of the hot-stamped body through precipitation strengthening. In order to obtain this effect, the Ti content is preferably set to 0.010% or more.

[0152] On the other hand, if the Ti content exceeds 0.100%, a large amount of carbonitride is generated in the steel, and the bendability of the hot-stamped body is reduced. Therefore, the Ti content is set to 0.100% or less.

[0153] B: 0 to 0.0100%

[0154] B increases the quenchability of the steel and increases the strength of the hot-stamped body. In order to obtain this effect, the B content is preferably set to 0.0015% or more.

[0155] On the other hand, if the B content exceeds 0.0100%, coarse carbides are generated, and the bendability of the hot-stamped body is deteriorated. Therefore, the B content is set to 0.0100% or less.

[0156] Mo: 0 to 1.00%

[0157] Mo increases the quenchability of the steel sheet and increases the strength of the hot-stamped body. In order to obtain this effect, the Mo content is preferably set to 0.05% or more.

[0158] On the other hand, if the Mo content exceeds 1.00%, coarse carbides are generated, and the bendability of the hot-stamped body is deteriorated. Therefore, the Mo content is set to 1.00% or less.

[0159] Co: 0 to 2.00%

[0160] Co increases the quenchability of the steel sheet and increases the strength of the hot-stamped body. In order to reliably exert this effect, the Co content is preferably set to 0.05% or more.

[0161] On the other hand, if the Co content exceeds 2.00%, coarse carbides are generated and the bendability of the hot press-formed body deteriorates. Therefore, the Co content is set to 2.00% or less.

[0162] Ni: 0% or more and less than 3.00%

[0163] Ni improves the quenchability of the steel sheet and improves the strength of the hot press-formed body. In order to obtain this effect, the Ni content is preferably set to 0.01% or more.

[0164] On the other hand, if the Ni content is 3.00% or more, segregation is promoted and the bendability of the hot press-formed body deteriorates. Therefore, the Ni content is set to less than 3.00%.

[0165] Cu: 0 to 1.00%

[0166] Cu, like Ni, improves the quenchability of the steel sheet and improves the strength of the hot press-formed body. In order to obtain this effect, the Cu content is preferably set to 0.01% or more.

[0167] On the other hand, if the Cu content exceeds 1.00%, segregation is promoted and the bendability of the hot press-formed body deteriorates. Therefore, the Cu content is set to 1.00% or less.

[0168] V: 0 to 1.00%

[0169] V improves the quenchability of the steel sheet and improves the strength of the hot press-formed body. In order to obtain this effect, the V content is preferably set to 0.01% or more.

[0170] On the other hand, if the V content exceeds 1.00%, coarse carbides are generated and the bendability of the hot press-formed body deteriorates. Therefore, the V content is set to 1.00% or less.

[0171] W: 0 to 1.000%

[0172] W improves the quenchability of the steel sheet and improves the strength of the hot press-formed body. In order to obtain this effect, the W content is preferably set to 0.001% or more.

[0173] On the other hand, if the W content exceeds 1.000%, segregation is promoted and the bendability of the hot press-formed body deteriorates. Therefore, the W content is set to 1.000% or less.

[0174] Ca: 0 to 0.010%

[0175] Ca improves the deformability by suppressing the generation of oxides that become the starting point of damage, and improves the bendability of the hot press-formed body. In order to reliably obtain this effect, the Ca content is preferably set to 0.001% or more.

[0176] On the other hand, if the Ca content exceeds 0.010%, coarse oxides are generated and the bendability of the hot press-formed body deteriorates. Therefore, the Ca content is set to 0.010% or less.

[0177] Mg: 0 to 1.000%

[0178] Mg improves the deformability by suppressing the generation of oxides that become the starting point of damage, and improves the bendability of the hot press-formed body. In order to obtain this effect, the Mg content is preferably set to 0.001% or more.

[0179] On the other hand, if the Mg content exceeds 1.000%, coarse oxides are generated and the bendability of the hot press-formed body deteriorates. Therefore, the Mg content is set to 1.000% or less.

[0180] REM: 0 to 1.000%

[0181] REM improves the deformability by suppressing the generation of oxides that become the starting point of damage, and improves the bendability of the hot press-formed body. In order to obtain this effect, the REM content is preferably set to 0.001% or more.

[0182] On the other hand, if the REM content exceeds 1.000%, coarse oxides are generated and the bendability of the hot press-formed body deteriorates. Therefore, the REM content is set to 1.000% or less.

[0183] Note that REM in the present embodiment refers to a total of 17 elements including Sc, Y, and lanthanoid elements, and the content of REM refers to the total content of these elements.

[0184] Sb: 0 to 1.000%

[0185] Sb improves the deformability by suppressing the generation of oxides that become the starting point of damage, and improves the bendability of the hot press-formed body. In order to obtain this effect, the Sb content is preferably set to 0.005% or more.

[0186] On the other hand, if the Sb content exceeds 1.000%, coarse oxides are generated and the bendability of the hot press-formed body deteriorates. Therefore, the Sb content is set to 1.000% or less.

[0187] Zr: 0 to 1.000%

[0188] Zr improves the deformability by suppressing the generation of oxides that become the starting point of damage, and improves the bendability of the hot press-formed body. In order to obtain this effect, the Zr content is preferably set to 0.001% or more.

[0189] On the other hand, if the Zr content is set to exceed 1.000%, coarse oxides are generated, and the flexibility of the hot-stamped part deteriorates. Therefore, the Zr content is set to 1.000% or less.

[0190] Sn: 0~1.000%

[0191] Sn enhances deformability and improves the flexibility of hot-stamped parts by inhibiting the formation of oxides that become the starting point of damage. To reliably achieve this effect, the Sn content is preferably set to 0.001% or more.

[0192] On the other hand, even with a large amount, the above effects are saturated, so the Sn content is set to 1.000% or less.

[0193] As: 0~0.100%

[0194] As improves the flexibility of hot-stamped articles by refining the old austenite grains by lowering the austenite single-phase temperature. To reliably achieve this effect, the As content is preferably set to 0.001% or more.

[0195] On the other hand, even if it contains a large amount, the above effects are saturated, so the As content is set to be below 0.100%.

[0196] The chemical composition of the aforementioned hot-stamping steel sheet can be determined using general analytical methods. For example, ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry) can be used. It should be noted that C and S are determined using the combustion-infrared absorption method, N using the inert gas melting-thermal conductivity method, and O using the inert gas melting-non-dispersive infrared absorption method. If the hot-stamping steel sheet has a coating on its surface, the chemical composition can be analyzed after removing the coating by mechanical grinding.

[0197] Next, the metal structure of the hot stamping steel sheet of this embodiment will be described.

[0198] The hot-stamping steel sheet of this embodiment has the following microstructure: ferrite area ratio S α and the area ratio S of granular bainite GB The total is S α +S GB The area ratio S of the above-mentioned granular bainite is 10% or more but less than 50%. GB The above-mentioned area ratio S of ferrite α The ratio is S GB / S αThe range is 0.30 to 0.70. The following explains each regulation.

[0199] It should be noted that, in this embodiment, the metal structure is specified in the section of the plate thickness parallel to the rolling direction, at a depth of 1 / 4 of the plate thickness from the surface (the region from 1 / 8 to 3 / 8 of the plate thickness from the surface). This is because the metal structure at this location exhibits the representative metal structure of the steel plate.

[0200] "Ferrite area fraction S" α and the area ratio S of granular bainite GB The total is S α +S GB "More than 10% and less than 50%"

[0201] If the area fraction of ferrite S α and the area ratio S of granular bainite GB The total is S α +S GB Below 10%, the old austenite grains cannot be granulated in hot stamping, resulting in the inability to obtain hot stamping parts with excellent flexibility. Because ferrite and granular bainite have low solid solution limits for carbon, by using S... α +S GB Set it to 10% or higher, and include S as described later. GB / S α Within a desired range, carbon diffuses towards the ferrite grain boundaries, forming carbon segregation regions within them. During hot stamping, these carbon segregation regions become the starting point for older austenite grains, leading to their uniform dispersion and formation. It is speculated that this results in the granulation of older austenite grains within the hot-stamped body. α +S GB Preferably, it is 20% or more, and more preferably 30% or more.

[0202] On the other hand, if S α +S GB If the concentration is above 50%, it excessively promotes carbon segregation in the ferrite grain boundaries, increasing the density of carbides in the ferrite grain boundaries. This carbides cannot be uniformly dispersed after hot stamping, resulting in the formation of old austenite grains. α +S GB Preferably below 40%.

[0203] "Area ratio of granular bainite S" GB With the ferrite area fraction S α The ratio is S GB / S α "0.30 to 0.70"

[0204] SGB / S α 0.30 to 0.70. Ferrite does not contain subgrain boundaries, and thus carbon is difficult to segregate in the grain, as compared with granular bainite. By controlling the area ratio of ferrite and granular bainite in the above range, the amount of carbon segregation in the ferrite grain boundaries can be increased. Subgrain boundaries contained in the crystal grains of granular bainite function as a starting point for carbon segregation, and thus function as a starting point for old austenite at the time of hot stamping heating. Thus, the average grain size of old austenite grains in the hot stamping molded body can be controlled to 25 μm or less.S GB / S α 0.40 or more is preferred.

[0205] On the other hand, if S GB / S α 0.70, carbon segregation into subgrain boundaries is excessively promoted, and the distance between adjacent austenite grains becomes close at the time of hot stamping heating, and thus the average grain size of old austenite grains cannot be controlled to 5 μm or more. Therefore, S GB / S α 0.70 or less. 0.50 or less is preferred.

[0206] In the metal structure of the hot stamping steel sheet of the present embodiment, the remaining portion is one or two or more kinds of pearlite, martensite, lower bainite, retained austenite, and tempered martensite. The area ratio of the remaining portion can be set to 50% or more and 90% or less, in accordance with the relationship with S α +S GB

[0207] Method for measuring the metal structure of the hot stamping steel sheet

[0208] A sample is cut from an arbitrary position of the hot stamping steel sheet, which is 50 mm or more from the end face (in the case where a sample cannot be collected from this position, a position avoiding the end portion). The size of the sample also varies depending on the measuring device, but is set to a size from which a cross section parallel to the rolling direction can be observed, of about 10 mm in the rolling direction.

[0209] ​After the cross section of the above sample was ground using silicon carbide paper #600 to #1500, the mirror surface was finished using a liquid obtained by dispersing diamond powder having a particle size of 1 to 6 μm in a diluent such as alcohol or pure water, and the fine grinding was performed by electrolytic polishing. Next, in a region of 100 μm in length and from 1 / 8 depth of the plate thickness to 3 / 8 depth of the plate thickness from the surface at an arbitrary position in the length direction of the cross section of the sample, the structure was observed using an apparatus composed of a thermal field emission type scanning electron microscope (JSM-7001F manufactured by JEOL) and an EBSD detector (DVC5 detector manufactured by TSL) in such a manner that the observable distance surface is 1 / 4 depth of the plate thickness. The scanning electron microscope used was set to a microscope equipped with 2 electron detectors. The acceleration voltage was 15 kV, and the irradiation current level was 13. The sample was irradiated with electron rays, and 2 electron images were photographed using a scanning electron microscope. -5 The sample was irradiated with electron rays in a vacuum of 1.0 x 10

[0210] In the obtained photographed image, the region in which the intragranular cementite was precipitated in lamellar form was determined to be pearlite. The lath-shaped crystal grains were determined to be lower bainite, martensite, and tempered martensite. Next, for the field of view, EBSD analysis was performed at an analysis speed of 200 to 300 points / second using an EBSD analysis apparatus. Using the "Grain Average Misorientation" function mounted in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis apparatus, the area ratio S α of ferrite and the area ratio S GB of granular bainite were calculated. With this function, for a crystal grain having a body-centered structure, the average value of the orientation difference between adjacent measurement points can be calculated for all measurement points in the crystal grain. With respect to the crystal orientation information obtained by EBSD analysis, the region surrounded by grain boundaries having an average crystal orientation difference of 5° or more was defined as a crystal grain, and the map was drawn by the "Grain Average Misorientation" function. In the region other than the regions determined to be pearlite, lower bainite, martensite, and tempered martensite from the map, the region in which the average crystal orientation difference in the crystal grain was less than 0.4° was determined to be ferrite, and the region in which the average crystal orientation difference in the crystal grain was 0.4° or more and 3.0° or less was determined to be granular bainite. The area ratio of ferrite was obtained by calculating the area ratio of the region determined to be ferrite. The area ratio of granular bainite was obtained by calculating the area ratio of the region determined to be granular bainite.

[0211] The hot-stamped steel sheet of the present embodiment can also have a plated layer formed on the surface, for the purpose of improving corrosion resistance and the like after hot stamping. The plated layer can be any one of an electroplated layer and a hot-dipped plated layer. The electroplated layer includes, for example, an electroplated zinc layer, an electroplated Zn-Ni alloy layer, and the like. The hot-dipped plated layer includes, for example, a hot-dipped zinc layer, an alloyed hot-dipped zinc layer, a hot-dipped aluminum layer, a hot-dipped Zn-Al alloy layer, a hot-dipped Zn-Al-Mg alloy layer, a hot-dipped Zn-Al-Mg-Si alloy layer, and the like. The amount of the plated layer is not particularly limited, and a general amount is preferable.

[0212] Further, the sheet thickness of the hot-stamped steel sheet of the present embodiment is not particularly limited, but is preferably set to 0.5 to 3.5 mm from the viewpoint of lightening the vehicle body and the like.

[0213] Next, the hot-stamped formed body of the present embodiment obtained by hot stamping the above-described hot-stamped steel sheet will be described. The hot-stamped formed body of the present embodiment has the same chemical composition as the above-described hot-stamped steel sheet. The method of measuring the chemical composition is preferably the same as that of the hot-stamped steel sheet. Further, the hot-stamped formed body of the present embodiment has the old austenite grains in the metal structure be refined. That is, the hot-stamped formed body of the present embodiment has a metal structure in which the average grain size of the old austenite grains is 5 to 25 μm, and the standard deviation of the grain size of the above-described old austenite grains is 0.1 to 2.0 μm.

[0214] Note that, in the present embodiment, the metal structure in the position of the depth of 1 / 4 of the sheet thickness from the surface (the region of the depth of 1 / 8 of the sheet thickness from the surface to the depth of 3 / 8 of the sheet thickness from the surface) of the cross section orthogonal to the sheet surface is defined. The reason for this is that the metal structure at this position exhibits representative metal structure of the hot-stamped formed body. Hereinafter, the metal structure will be described.

[0215] "the average grain size of the old austenite grains is 5 to 25 μm"

[0216] "the standard deviation of the grain size of the old austenite grains is 0.1 to 2.0 μm"

[0217] In the metal structure of the hot-stamped formed body, by setting the average grain size of the old austenite grains to 5 to 25 μm, and setting the standard deviation of the grain size of the old austenite grains to 0.1 to 2.0 μm, the bendability of the hot-stamped formed body can be improved. If the average grain size of the old austenite grains or the standard deviation of the grain size of the old austenite grains is outside the above-described range, excellent bendability cannot be obtained in the hot-stamped formed body.

[0218] The average grain size of the old austenite grains is preferably set to 10 μm or more, and more preferably 15 μm or more. Further, the average grain size of the old austenite grains is preferably set to 20 μm or less.

[0219] By setting the standard deviation of the particle diameter of the prior austenite grains to 2.0 μm or less, excellent bendability can be obtained in the hot press-formed body. Therefore, the standard deviation of the particle diameter of the prior austenite grains is set to 2.0 μm or less. More preferably, 1.2 μm or less, further preferably 1.1 μm or less, and still further preferably 0.4 μm or less.

[0220] In actual operation, it is difficult to set the standard deviation of the particle diameter of the prior austenite grains to less than 0.1 μm, and thus the substantial lower limit becomes 0.1 μm or more.

[0221] If the area ratio of the prior austenite grains having an average particle diameter of 0.5 to 3.0 μm is 60% or less, more excellent bendability can be obtained in the hot press-formed body. Therefore, the area ratio of the prior austenite grains having an average particle diameter of 0.5 to 3.0 μm can also be set to 60% or less. More preferably, 50% or less, and further preferably 40% or less.

[0222] Method for measuring average particle diameter and standard deviation of particle diameter of prior austenite grains

[0223] Next, a method for measuring the average crystal grain diameter of the prior austenite grains will be described. A sample is cut from an arbitrary position of the hot press-formed body that is 50 mm or more from the end face (in the case where a sample cannot be collected from this position, a position avoiding the end portion) in a manner that enables observation of a cross section of the thickness parallel to the rolling direction. The size of the sample varies depending on the measuring device, but is set to a size that enables observation of about 10 mm in the rolling direction. After the cross section of the sample is ground using a silicon carbide paper of #600 to #1500, the surface is finished to a mirror surface using a liquid obtained by dispersing diamond powder having a particle size of 1 to 6 μm in a diluent such as alcohol or pure water, and the mirror surface is subjected to fine grinding using electrolytic polishing.

[0224] Next, in a region from a position 1 / 8 depth from the surface to a position 3 / 8 depth from the surface in the thickness direction at an arbitrary position in the length direction of the sample cross section in a manner that enables observation of a position 1 / 4 depth from the surface, a region of 100 μm in length and 100 μm in the thickness direction is subjected to analysis using a device composed of a hot field emission type scanning electron microscope (JSM-7001F manufactured by JEOL) and an EBSD detector (DVC5 manufactured by TSL) at a resolution speed of 9.6 x 10 -5 The sample was irradiated with electron rays at an acceleration voltage of 15 kV and a irradiation current level of 13 in a vacuum of 1 x 10 The crystal orientation of the prior austenite grains was calculated from the crystal orientation relationship between the general prior austenite grains and the crystal grains having a body-centered structure after the phase change, and the average crystal grain diameter of the prior austenite grains was calculated using the same.

[0225] The method of calculating the crystal orientation of the old austenite grains is not particularly limited, but for example, the crystal orientation of the old austenite grains is calculated by the method described in Non-Patent Literature 1, and the crystal orientation of the old austenite in each coordinate of the region where EBSD measurement is performed is determined. Next, using the "Inverse Pole Figure" function mounted in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device, a crystal orientation map of the old austenite grains is created. For one old austenite grain contained in the observation field, the average of the shortest diameter and the longest diameter is calculated, and the average is taken as the grain size of the old austenite grain. The above operation is performed on all old austenite grains except for the old austenite grains that do not contain the entire crystal grains in the photographed field of view such as the end portion of the photographed field of view, and the grain size of all old austenite grains in the photographed field of view is calculated. The average grain size of the old austenite grains in the photographed field of view is obtained by calculating the sum of the grain sizes of the old austenite grains obtained divided by the total number of old austenite grains for which the grain size is measured. This operation is performed for each field of view of all photographed fields of view, and the average grain size of the old austenite grains is obtained by calculating the average grain size of the old austenite grains of all photographed fields of view.

[0226] The standard deviation of the grain size of the old austenite grains is obtained by calculating the standard deviation from the grain size of the old austenite grains. At this time, in order to exclude the influence of fine grains and coarse grains generated locally, the standard deviation is calculated excluding the minimum value and the maximum value of the old austenite grain size.

[0227] The area rate of the old austenite grains having an average grain size of 0.5 to 3.0 μm is obtained by calculating the value obtained by dividing the area of the old austenite grains having an average grain size of 0.5 to 3.0 μm by the area of the entire measurement field.

[0228] The metal structure of the hot-stamped molded body is not particularly limited as long as the desired strength and bendability can be obtained after hot stamping, but for example, it can contain ferrite: 0 to 50%, bainite and martensite: 0 to 100%, pearlite: 0 to 30%, and retained austenite: 0 to 5% in area %. The metal structure of the hot-stamped molded body can be measured by the following method.

[0229] Method of measuring the metal structure of the hot-stamped molded body

[0230] A sample was cut so as to observe a cross section perpendicular to the plate surface from a position of 50 mm or more from the end face of the hot press-formed body (in a case where a sample cannot be collected from this position, a position avoiding the end portion). After the cross section of the sample was polished using a silicon carbide paper of #600 to #1500, mirror finishing was performed using a liquid obtained by dispersing diamond powder having a particle size of 1 to 6 μm in a diluent such as alcohol or pure water, and nitric acid ethanol etching was performed. A photograph was taken of a plurality of fields of view in a region of 50 μm in length and from a depth of 1 / 8 of the plate thickness to a depth of 3 / 8 of the plate thickness from the surface at an arbitrary position in the length direction of the sample cross section using a thermal field emission type scanning electron microscope (JSM-7001F manufactured by JEOL). A grid of equal intervals was drawn on the photograph, and the structure at the grid points was identified. The number of grid points corresponding to each structure was counted, and divided by the total number of grid points, thereby obtaining the area ratio of each structure. The more the total number of grid points, the more accurately the area ratio can be calculated. In the present embodiment, the grid pitch was set to 2 μm x 2 μm, and the total number of grid points was set to 1500 points.

[0231] A region in which intragranular cementite was precipitated in a lamellar shape was judged to be pearlite. A region in which the brightness was small and no lower structure was observed was judged to be ferrite. A region in which the brightness was large and no lower structure appeared by etching was judged to be martensite and retained austenite. A region not satisfying any of the above was judged to be bainite.

[0232] The area ratio of the martensite was obtained by subtracting the area ratio of the retained austenite obtained by the EBSD analysis described later from the area ratio of the martensite and the retained austenite obtained from the photograph described above.

[0233] The area ratio of the retained austenite was measured by backscattered electron diffraction image (EBSD). The analysis using EBSD was performed on a region from a depth of 1 / 8 of the plate thickness to a depth of 3 / 8 of the plate thickness from the surface using a sample collected at the same sample collection position as the measurement using the photograph described above. The sample was set to a sample that was mirror finished after polishing using a silicon carbide paper of #600 to #1500, using a liquid obtained by dispersing diamond powder having a particle size of 1 to 6 μm in a diluent such as alcohol or pure water, and was further mirror finished by electrolytic polishing in order to sufficiently remove the strain of the measurement cross section. Note that, in the electrolytic polishing, the mechanical polishing strain of the observation surface was removed by polishing of 20 μm at the minimum and 50 μm at the maximum. If the collapse of the end portion is considered, it is preferable to be 30 μm or less.

[0234] The measurement using EBSD was performed with an acceleration voltage set to 15 to 25 kV at intervals of at least 0.25 μm or less to obtain crystal orientation information of each measurement point in a range of 150 μm or more in the sheet thickness direction and 250 μm or more in the rolling direction. In the obtained crystal structure, the area where the crystal structure was fcc was determined to be retained austenite using the "Phase Map" function mounted in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device. The area ratio of the retained austenite was obtained by calculating the ratio of the measurement points determined to be retained austenite. Here, the more the number of measurement points, the more preferable, and therefore, the narrower the measurement interval, and furthermore, the wider the measurement range are better. However, in the case where the measurement interval is less than 0.01 μm, the adjacent points interfere within the wide range of the electron beam. Therefore, the measurement interval was set to 0.01 μm or more. Furthermore, the measurement range was set to 200 μm or more in the sheet thickness direction and 400 μm or more in the sheet width direction at the maximum. Furthermore, in the measurement, an EBSD device composed of a hot field emission type scanning electron microscope (JSM-7001F manufactured by JEOL) and an EBSD detector (DVC5-type detector manufactured by TSL) was used. At this time, the degree of vacuum in the device was set to 9.6 x 10 -5 The irradiation current level was set to 13 and the irradiation level of the electron beam was set to 62 at a vacuum degree of 9.6 x 10

[0235] The hot press-formed body of the present embodiment can also have a plated layer formed on the surface in order to improve corrosion resistance and the like after hot press forming. The plated layer can be any one of an electroplated layer and a hot-dipped plated layer. The electroplated layer includes, for example, an electroplated zinc layer, an electroplated Zn-Ni alloy layer, and the like. The hot-dipped plated layer includes, for example, a hot-dipped zinc layer, an alloyed hot-dipped zinc layer, a hot-dipped aluminum layer, a hot-dipped Zn-Al alloy layer, a hot-dipped Zn-Al-Mg alloy layer, a hot-dipped Zn-Al-Mg-Si alloy layer, and the like. The amount of the plated layer is not particularly limited, and a general amount is preferable.

[0236] The sheet thickness of the hot press-formed body of the present embodiment is not particularly limited, but is preferably set to 0.5 to 3.5 mm from the viewpoint of lightening the vehicle body and the like.

[0237] The tensile (maximum) strength of the hot press-formed body of the present embodiment is 2200 MPa or more. It is preferably 2400 MPa or more, and more preferably 2550 MPa or more. The tensile strength was calculated according to the test method described in JIS Z 2241:2011 by preparing a No. 5 test piece described in JIS Z 2241:2011 from a position as flat as possible of the hot press-formed body.

[0238] Further, the hot press-formed body of the present embodiment preferably has a maximum bending angle of 20° or more, obtained by a bending test based on the VDA standard (VDA 238-100) prescribed by the German Automotive Industry Association. More preferably, it has a maximum bending angle of 30° or more or 40° or more. The conditions in the bending test are set as follows.

[0239] Test piece size: 60 mm (rolling direction) x 30 mm (direction parallel to the plate width direction)

[0240] Test piece plate thickness: 1.6 mm

[0241] Bending ridge: direction parallel to the plate width direction

[0242] Test method: roll support, punch press-in

[0243] Roll diameter: φ 30 mm

[0244] Punch shape: tip R = 0.4 mm

[0245] Roll distance: 2.0 x plate thickness (mm) + 0.5 mm

[0246] Press-in speed: 20 mm / min

[0247] Testing machine: SHIMADZU AUTOGRAPH 20 kN

[0248] Next, the manufacturing method of the hot press steel sheet of the present embodiment will be described.

[0249] In the manufacturing method of the hot press steel sheet of the present embodiment, in order to obtain a hot press steel sheet having the above-described metal structure, it is preferable to set the final reduction rate of the finish rolling in the hot rolling to 40 to 80%. Generally, the final reduction rate of the finish rolling is less than 10%, but in the present embodiment, it is preferable to set a final reduction rate higher than the general final reduction rate.

[0250] The billet (steel material) to be subjected to the hot rolling can be a billet manufactured by a conventional method, for example, a continuously cast slab or a billet manufactured by a general method such as a thin slab continuous casting machine. Further, in the casting step, it is also possible to perform rolling with a reduction rate of 30 to 70% in a temperature range in which the center temperature of the billet after solidification is 1200°C or more and the solidus temperature or less. By this, segregation of Mn can be moderated, and the bendability in the hot press-formed body can be improved. Note that the solidus temperature can be calculated from the following formula (1).

[0251] Solidus temperature (°C) = 1536 - (415.5 x %C + 12.3 x %Si + 6.8 x %Mn + 124.5 x %P + 183.9 x %S + 4.3 x %Ni + 1.4 x %Cr + 4.1 x %Al) (1)

[0252] Note that in the above formula (1), %C, %Si, %Mn, %P, %S, %Ni, %Cr, and %Al mean the content (mass %) of each element.

[0253] In the hot rolling, rough rolling and finish rolling are performed. In the finish rolling, the slab after the rough rolling is rolled by a plurality of finishing mills. In the present embodiment, it is preferable to perform the finish rolling in such a manner that the reduction ratio in the final pass of the finish rolling (final reduction ratio) becomes 40% or more. When the sheet thickness before the final pass of the finish rolling is set to t0 and the sheet thickness after the final pass of the finish rolling is set to t1, the final reduction ratio can be represented by {(t0-t1) / t0} x 100 (%).

[0254] By setting the final reduction ratio of the finish rolling to 40 to 80%, the old austenite grains are refined and the starting points of ferrite and granular bainite increase. Thereby, in the metal structure of the hot stamping steel sheet, S α +S GB and S GB / S α are set to the desired range. If the final reduction ratio of the finish rolling is less than 40%, in the metal structure of the hot stamping steel sheet, S α +S GB and S GB / S α cannot be set to the desired range. Therefore, the final reduction ratio of the finish rolling is preferably set to 40% or more. The final reduction ratio of the finish rolling is preferably 50% or more. On the other hand, if the final reduction ratio of the finish rolling exceeds 80%, S GB / S α cannot be controlled to 0.70 or less. Therefore, the final reduction ratio of the finish rolling is preferably set to 80% or less. More preferably, it is less than 70%.

[0255] Note that the heating temperature and the holding time of the billet before the hot rolling are not particularly limited, but it is preferable to be held for 20 minutes or more in a temperature region of 1200°C or higher.

[0256] After the finish rolling, it is preferable to be coiled in a temperature region of 400 to 750°C. If the coiling temperature exceeds 750°C, the ferrite phase transformation is excessively promoted and S α +S GB becomes 50% or more, S GB / S αbecomes lower than 0.30. The coiling temperature is preferably 700°C or lower, more preferably 660°C or lower.

[0257] Further, the coiling temperature is preferably 400°C or higher. If the coiling temperature is lower than 400°C, the generation of granular bainite is suppressed and the S GB / S α becomes lower than 0.30. The coiling temperature is preferably 450°C or higher, more preferably 530°C or higher.

[0258] Further, after the finish rolling (after the completion of the hot rolling), cooling is preferably performed after 2.5 seconds or more. The cooling referred to here does not include air cooling, and is cooling at an average cooling rate of 50 to 200°C / s. If the time from the finish rolling to the start of the cooling is less than 2.5 seconds, the desired amount of S α +S GB .

[0259] After the coiling, cold rolling can also be performed as necessary. Further, the plating layer described above can also be formed after the finish rolling or the cold rolling. Furthermore, pickling can also be performed between the hot rolling and the cold rolling. In the cold rolling, it is only necessary to set the usual cumulative reduction rate, for example, 30 to 90%. Further, the temper rolling can also be performed under the usual conditions. Further, in order to soften the hot rolled steel sheet, the hot rolled sheet annealing in which the hot rolled steel sheet is heated to a temperature region of 730°C or lower can also be performed.

[0260] By the above method, the hot press forming steel sheet of the present embodiment can be manufactured. Next, the manufacturing method of the hot press formed body of the present embodiment, which can be manufactured using the above hot press forming steel sheet, will be described. The manufacturing method of the hot press formed body of the present embodiment is not particularly limited, but for example, the manufacturing method described below can be set.

[0261] First, the above hot press forming steel sheet is heated to a temperature region of 800°C or higher. If the heating temperature is lower than 800°C, sometimes the coarse carbide remains during the heating and the bendability of the hot press formed body decreases. The heating temperature is preferably 820°C or higher, more preferably 860°C or higher.

[0262] The upper limit of the heating temperature is not particularly limited, but if the heating temperature is too high, decarburization is promoted in the surface layer of the steel sheet and the strength of the hot press formed body decreases. Therefore, the heating temperature is preferably 1000°C or lower, more preferably 960°C or lower, still more preferably 930°C or lower.

[0263] Further, the holding time at the above heating temperature is preferably set to 1.0 to 10.0 minutes. If the holding time is less than 1.0 minute, sometimes coarse carbides remain and the bendability of the hot press-formed body decreases. On the other hand, if the holding time exceeds 10.0 minutes, sometimes decarburization is promoted in the surface layer of the steel sheet and the strength of the hot press-formed body decreases.

[0264] Further, the average heating rate up to the above heating temperature is preferably set to 1.0°C / s or more. If the average heating rate is less than 1.0°C / s, decarburization is promoted in the surface layer of the steel sheet and the strength of the hot press-formed body decreases. The upper limit is not particularly specified, but it is practically difficult to set to more than 1000°C / s, and thus 1000°C / s or less becomes a substantial upper limit.

[0265] After the above heating and holding, hot press forming is performed. After the hot press forming, for example, cooling is preferably performed at an average cooling rate of 10°C / s or more until the temperature region of 300°C or less. If the average cooling rate is less than 10°C / s, sometimes the strength is insufficient. The upper limit is not particularly specified, but it is practically difficult to set to more than 1000°C / s, and thus 1000°C / s or less becomes a substantial upper limit.

[0266] Note that, in the heating at the time of hot press forming, preheating, that is, heating in two stages, is not preferable. This is because the segregation region of carbon at the grain boundaries of the stage-made of the hot press forming steel sheet is eliminated, and old austenite grains are generated without being uniformly dispersed, as a result, the standard deviation of the old austenite grains cannot be controlled within the desired range.

[0267] By the above-described preferred production method, the hot press-formed body of the present embodiment can be obtained. Note that, after the hot press forming, a tempering treatment at 150 to 600°C can be performed. Further, a softened region can be provided in part of the hot press-formed body by tempering by laser irradiation or the like. In the softened region, the weldability is improved. For example, if the end portion of the hot press-formed body is softened and spot welding is performed, the strength difference between the softened end portion and the spot-welded portion in the end portion can be reduced, and thus the damage from the interface between the two can be suppressed. Further, for example, in the case where the hot press-formed body is applied to a high-strength member of an automobile, by providing a softened region in part of the high-strength member, the damage and the deformation mode of the high-strength member at the time of a collision can be controlled.

[0268] Example

[0269] Next, an example of the present application will be described, but the conditions in the example are an example of conditions adopted in order to confirm the workability and effects of the present application, and the present application is not limited to this example of conditions. The present application can adopt various conditions as long as the gist of the present application is not deviated from and the object of the present application is achieved.

[0270] The steel billets produced by casting the molten steel having the chemical compositions shown in Tables 1A to 1D were heated, held at a temperature region of 1200°C or higher and lower than 1350°C for 20 minutes or more, and then hot-rolled, cooled and coiled under the conditions shown in Tables 2A to 2F, and cold-rolled, hot-rolled sheet-annealed, pickled and plated as necessary. Thus, hot-stamping steel sheets shown in Tables 2A to 2F were obtained. Note that the average cooling rate of the cooling from the finish rolling to the coiling was set to 50 to 200°C / s. Further, the cooling at the above average cooling rate was performed after 2.5 seconds or more from the finish rolling. Among them, Steel Sheet No. 172 was cooled after 2.0 seconds from the finish rolling.

[0271] Note that Steel Sheet No. 107 was subjected to rolling with a reduction rate of 30 to 70% in a temperature region where the center temperature of the slab after solidification was lower than the solidus temperature in the casting step.

[0272] Steel Sheet No. 108 was set to a heating temperature of 1350°C before the hot rolling.

[0273] Steel Sheet No. 125 was subjected to hot-rolled sheet annealing with heating to a temperature region of 730°C or lower and holding.

[0274] Steel Sheet No. 126 was not subjected to cold rolling.

[0275] Steel Sheet No. 127 was formed with an electro-galvanized layer on the surface.

[0276] Steel Sheet No. 128 was formed with an electro-galvanized Zn-Ni alloy layer on the surface.

[0277] Steel Sheet No. 129 was formed with a hot-dip galvanized layer on the surface.

[0278] Steel Sheet No. 130 was formed with an alloyed hot-dip galvanized layer on the surface.

[0279] Steel Sheet No. 131 was formed with a hot-dip aluminum plated layer on the surface.

[0280] Steel Sheet No. 132 was formed with a hot-dip galvanized Zn-Al alloy layer on the surface.

[0281] Steel Sheet No. 133 was formed with a hot-dip galvanized Zn-Al-Mg alloy layer on the surface.

[0282] Steel Sheet No. 134 was formed with a hot-dip galvanized Zn-Al-Mg-Si alloy layer on the surface.

[0283] The obtained hot-stamping steel sheets were hot-stamped under the conditions described in Tables 3A to 3F, and hot-stamping molded bodies shown in Tables 3A to 3F were obtained.

[0284] Manufacture No. 161 was subjected to a tempering treatment at 150 to 600°C after hot stamping.

[0285] Manufacture No. 162 was formed with a partially softened region by laser irradiation to a part of a hot-stamped body and tempering.

[0286] Manufacture No. 163 was subjected to hot stamping after heating to the heating temperature described in Table 3F, cooling to a temperature region of 250°C or lower, and then heating to 900°C, and was cooled at the average cooling rate described in Table 3D.

[0287] Note that in the present application examples of Tables 2A to 2F, the remaining portion of the microstructure was one or two or more of pearlite, martensite, lower bainite, retained austenite, and tempered martensite, and the total area ratio of these was more than 50% and 90% or less. Further, in the present application examples of Tables 3A to 3F, the metal structure included, in area %, ferrite: 0 to 50%, bainite and martensite: 0 to 100%, pearlite: 0 to 30%, and retained austenite: 0 to 5%.

[0288] Further, the measurement method of the metal structure of the hot-stamped steel sheet, and the measurement method of the metal structure and mechanical properties of the hot-stamped body were set as described above. In the case where the tensile strength of the hot-stamped body was 2200 MPa or more, it was set to have high strength, and was judged to be acceptable, and in the case where the tensile strength was less than 2200 MPa, it was set to not have high strength, and was judged to be unacceptable.

[0289] Further, in the case where the maximum bending angle was 20° or more, it was set to have excellent bendability, and was judged to be acceptable, and in the case where the maximum bending angle was less than 20°, it was set to not have excellent bendability, and was judged to be unacceptable.

[0290]

[0291]

[0292]

[0293]

[0294] Table 2A

[0295]

[0296] Underlined indicates out of the scope of the present application or manufacturing conditions are not preferable.

[0297] Table 2B

[0298]

[0299] Underline indicates out of the scope of the present invention or manufacturing condition is not preferred.

[0300] Table 2C

[0301]

[0302] Underline indicates out of the scope of the present invention or manufacturing condition is not preferred.

[0303] Table 2D

[0304]

[0305] Underline indicates out of the scope of the present invention or manufacturing condition is not preferred.

[0306] Table 2E

[0307]

[0308] Underline indicates out of the scope of the present invention or manufacturing condition is not preferred.

[0309] Table 2F

[0310]

[0311] Underline indicates out of the scope of the present invention or manufacturing condition is not preferred.

[0312]

[0313]

[0314]

[0315]

[0316]

[0317]

[0318] If Tables 3A to 3F are observed, it is learned that the hot press-formed bodies of the examples of the present invention have high strength and excellent bendability. On the other hand, it is learned that the hot press-formed bodies of the comparative examples have some property deteriorated.

[0319] Industrial applicability

[0320] According to the above-described aspect of the present invention, it is possible to provide a hot press-formed body having high strength and excellent bendability, and a hot press steel sheet capable of manufacturing the hot press-formed body.

Claims

1. A hot-stamped steel sheet characterized by, Chemical composition contains, in mass %: C: more than 0.40% and 0.70% or less, Si: 0.010 to 1.30%, Mn: more than 0.60% and 3.00% or less, P: 0.100% or less, S: 0.0100% or less, N: 0.0130% or less, O: 0.0200% or less, Al:0.0010~0.500%、 Cr:0.010~0.80%、 Nb: 0 to 0.100%, Ti: 0 to 0.100%, B:0~0.0100%、 Mo: 0 to 1.00%, Co: 0 to 2.00%, Ni: 0% or more and less than 3.00%, Cu: 0 to 1.00%, V:0~1.00%、 W:0~1.000%、 Ca: 0 to 0.010%, Mg: 0 to 1.000%, REM: 0 to 1.000%, Sb: 0 to 1.000%, Zr:0~1.000%、 Sn: 0 to 1.000%, and As: 0 to 0.100%, the remainder being Fe and impurities, has a metal structure in which the area ratio S of ferrite α and the area ratio S of granular bainite GB total of S α +S GB is 10% or more and less than 50%, The area ratio S of the granular bainite GB The area ratio S of the ferrite α The ratio S GB / S α is 5 / 12 to 7 / 10.

2. The hot-stamped steel sheet according to claim 1, characterized in that, the chemical composition contains, in mass %, one or two or more selected from the group consisting of Nb: 0.001 to 0.100%, Ti: 0.010 to 0.100%, B:0.0015~0.0100%、 Mo: 0.05 to 1.00%, Co: 0.05 to 2.00%, Ni: 0.01% or more and less than 3.00%, Cu: 0.01 to 1.00%, V:0.01~1.00%、 W:0.001~1.000%、 Ca: 0.001 to 0.010%, Mg: 0.001 to 1.000%, REM: 0.001 to 1.000%, Sb: 0.005 to 1.000%, Zr:0.001~1.000%、 Sn: 0.001 to 1.000%, and As: 0.001 to 0.100%. Chemical composition contains, in mass %:

3. The hot-stamped steel sheet according to claim 1, characterized in that, C: more than 0.40% and 0.70% or less, Si: 0.010 to 1.30%, Mn: more than 0.60% and 3.00% or less, P: 0.100% or less, S: 0.0100% or less, N: 0.0100% or less, O: 0.0200% or less, Nb: 0 to 0.100%, Al:0.0010~0.500%、 Cr:0.010~0.80%、 Ti: 0 to 0.100%, Mo: 0 to 1.00%, B:0~0.0100%、 Co: 0 to 2.00%, Ni: 0% or more and less than 3.00%, Cu: 0 to 1.00%, Ca: 0 to 0.010%, V:0~1.00%、 W:0~1.000%、 Mg: 0 to 1.000%, REM: 0 to 1.000%, Sb: 0 to 1.000%, and the remainder being Fe and impurities. Zr:0~1.000%, Chemical composition contains, in mass %: C: more than 0.40% and 0.70% or less, 4. A hot press-formed body, characterized by, Si: 0.010 to 1.30%, Mn: more than 0.60% and 3.00% or less, P: 0.100% or less, S: 0.0100% or less, N: 0.0130% or less, O: 0.0200% or less, Nb: 0 to 0.100%, Al:0.0010~0.500%、 Cr:0.010~0.80%、 Ti: 0 to 0.100%, Mo: 0 to 1.00%, B:0~0.0100%、 Co: 0 to 2.00%, Ni: 0% or more and less than 3.00%, Cu: 0 to 1.00%, Ca: 0 to 0.010%, V:0~1.00%、 W:0~1.000%、 Mg: 0 to 1.000%, REM: 0 to 1.000%, Sb: 0 to 1.000%, Sn: 0 to 1.000%, and Zr:0~1.000%、 As: 0 to 0.100%, the remainder being Fe and impurities. the remainder being Fe and impurities, a metal structure having old austenite grains with an average grain diameter of 5 to 25 μm and a standard deviation of the grain diameter of the old austenite grains of 0.1 to 2.0 μm, a tensile strength of 2200 MPa or more.

5. The hot-stamped body according to claim 4, characterized in that, the chemical composition contains, in mass %, Nb: 0.001 to 0.100%, Ti: 0.010 to 0.100%, B:0.0015~0.0100%、 Mo: 0.05 to 1.00%, Co: 0.05 to 2.00%, Ni: 0.01% or more and less than 3.00%, Cu: 0.01 to 1.00%, V:0.01~1.00%、 W:0.001~1.000%、 Ca: 0.001 to 0.010%, Mg: 0.001 to 1.000%, REM: 0.001 to 1.000%, Sb: 0.005 to 1.000%, Zr:0.001~1.000%、 Sn: 0.001 to 1.000%, As: 0.001 to 0.100% one or two or more kinds selected from the group consisting of 6. The hot-stamped body according to claim 4, characterized in that, the chemical composition contains, in mass %: C: more than 0.40% and 0.70% or less, Si: 0.010 to 1.30%, Mn: more than 0.60% and 3.00% or less, P: 0.100% or less, S: 0.0100% or less, N: 0.0100% or less, O: 0.0200% or less, Al:0.0010~0.500%、 Cr:0.010~0.80%、 Nb: 0 to 0.100%, Ti: 0 to 0.100%, B:0~0.0100%、 Mo: 0 to 1.00%, Co: 0 to 2.00%, Ni: 0% or more and less than 3.00%, Cu: 0 to 1.00%, V:0~1.00%、 W:0~1.000%、 Ca: 0 to 0.010%, Mg: 0 to 1.000%, REM: 0 to 1.000%, Sb: 0 to 1.000%, Zr:0~1.000%, the remainder being Fe and impurities.

7. The hot press-formed body according to any one of claims 4 to 6, characterized by the area ratio of the old austenite grains with an average grain diameter of 0.5 to 3.0 μm is 60% or less.

Citation Information

Patent Citations

  • Electronic apparatus

    JP2021081620A

  • Hot stamp molded body and method for producing same

    WO2018134874A1

  • Steel sheet

    CN110139941A

  • Steel sheet for hot stamping use

    WO2020195012A1